The Effect of the Project-Based Learning Model on Students’ Resilience During the Pandemic Covid-19 - Rahayu, Galih Dani Septiyan; Fauzi, Muhammad Rizal (JPI (Jurnal Pendidikan Indonesia), 2020)
This research is motivated by a change in the implementation of learning that is usually face-to-face in the classroom to learning through online due to the pandemic covid-19. Therefore this study was conducted aiming to analyze the effect of online-based project based learning learning model on the resilience of students during the pandemic Covid-19. The research method used was pre-experimental with the design of one group pretest-posttest. The research population was consisting of four classes with a total of 183 students. While the sample used was only 92 students. The instruments used in this study were questionnaire instruments in accordance with indicators of resilience which were then processed statistically to answer the problem formulation in this study. The results of this study are the online-based project-based learning model that has a positive influence on student resilience while studying in the covid pandemic 19.